Implementation of Educational Organization Diagnosis in Junior High Schools - Umi Anugerah Izzati; Olievia Prabandini Mulyana (International Journal of Current Educational Research, 2022)
This study aims to carry out an educational organizational diagnosis in junior high schools. The method used in this research is quantitative. Data collection was carried out by distributing the instrument to the subject. The instrument was compiled using an organizational diagnosis scale developed by the research team based on the Weisboard Concept. The subjects of this study were 40 teachers who worked in one of the junior high schools in Surabaya. Teachers who are the subject of research in this school have a minimum working period of one year—the data analysis techniques using descriptive statistics. The results of this study indicate that in junior high school, most aspects consisting of goals, structure, leadership, relationships, and helpful mechanisms are already in the high category. While the reward aspect needs to be improved further. Therefore, in the future, this school needs to improve a better reward system so that this school becomes better.